Original paperConduction abnormalities and arrhythmias after transcatheter closure of atrial septal defect with the Amplatzer Septal Occluder - Pieculewicz, Monika; Podolec, Piotr; Przewłocki, Tadeusz; Olszowska, Maria; Żmudka, Krzysztof; Tracz, Wiesława (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2006)
Isolated Atrial Septal Defects (ASD) constitute the second most common congenital heart lesion in both adult and paediatric populations. Conduction abnormalities and arrhythmias may occur in patients following secundum atrial septal defect (ASD) closure using the Amplatzer Septal Occluder (ASO). Therefore the aim of the study was to prospectively perform ambulatory 24-hour ECG monitoring to assess the electrocardiographic effects of transcatheter closure of ASD using the ASO. Methods: 35 consecutive adult subjects (23F, 12M; mean age: 42.7±12.7) were enrolled in the study, with a view to performing ASD II closure with the ASO device. Holter monitoring was performed on all patients before the procedure and at 1, 6 and 12 months of follow-up. Holter analysis included heart rate (HR), ECG intervals, supraventricular ectopy (SVE), ventricular ectopy (VE), and AV block. Results: The ASO devices were successfully implanted in all subjects, the procedure causing no serious complications. During the procedure in 2 (5.7%) cases transient supraventricular arrhythmia and in 1 (2.86%) case bradycardia to 30/min occurred. In 2 (5.7%) cases haematoma was observed around the place of puncture of the femoral artery. The diameter of the implanted devices ranged from 13 to 40 mm (mean 23.9±6.5 mm). A significant increase of supraventricular ectopy (SVE) was noted 1 month after the procedure. Additional supraventricular arrhythmias were observed in 25 (71.4%) cases. There was a reduction of supraventricular arrhythmias within the follow-up period, whereas at 12 months after the procedure the SVE value was similar to the baseline data. A significant increase in the number of SVE premature beats/24 h was noted 1 month after the procedure. There was a regression in the number of periprocedural supraventricular arrhythmias within the follow--up period, whereas after 12 months of ASD II closure there were no significant differences with the baseline data (435±198 vs 534±187; NS). There was no change in the mean number of ventricular arrhythmias/24h after the procedure. Conclusions 1. Transcatheter closure of secundum ASD is associated with a transient increase in supraventricular premature beats and a small risk of AV conduction abnormalities and paroxysmal atrial fibrillation in the early follow-up. There is a regression of periprocedural arrhythmias after 6 months of ASD closure. 2. Transcatheter closure of secundum ASD does not reduce arrhytmias, that are present prior ASD II close.